Critique session in art & design studio – a framework for art education / Zuhaili Akmal Ismail - Ismail, Zuhaili Akmal (Institute of Graduate Studies, UiTM, 2017)
Critique session for art students is for good ideas to emerge while simultaneously refining the feedback necessary to resolve any problems within the students’ design work. Unfortunately, students and art educators perceived this session as a daunting process due to the non-existent strategies or frameworks in creating a positive and collaborative learning approach for both parties. Moreover, for art educators in Malaysia, there are no references for the general guideline to good practices in critique session in the documents provided by the Malaysia Qualifications Agency (MQA) Code of Practice for Programme Accreditation (COPPA) and the Code of Practice for Institutional Audit (COPIA). This research is a mixed methods research which utilized both qualitative and quantitative methods that identify factors that contribute to student satisfaction and dissatisfaction in the existing critique session, design and develop a critique session framework for the teaching and learning in art & design studio and evaluate the effectiveness of the new framework for the teaching and learning in art & design studio.